2017
DOI: 10.1155/2017/8184160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bacterial Diversity in the Human Tongue Coating Based on Genus-Specific Primers for 16S rRNA Sequencing

Abstract: The characteristics of tongue coating are very important symbols for disease diagnosis in traditional Chinese medicine (TCM) theory. As a habitat of oral microbiota, bacteria on the tongue dorsum have been proved to be the cause of many oral diseases. The high-throughput next-generation sequencing (NGS) platforms have been widely applied in the analysis of bacterial 16S rRNA gene. We developed a methodology based on genus-specific multiprimer amplification and ligation-based sequencing for microbiota analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The tongue inspection is a procedure that has been reported from the Shang Dynasty (from 1600 BC to 1000 BC) that should be performed by the clinical observation the tongue body to evaluate its morphological and color homogeneity. In accordance to the Traditional Chinese Medicine, the tongue is able to absolve a key role of a biosensor, while the different tongue regions are able to provide information to check the diagnosis the organ systems health [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The tongue inspection is a procedure that has been reported from the Shang Dynasty (from 1600 BC to 1000 BC) that should be performed by the clinical observation the tongue body to evaluate its morphological and color homogeneity. In accordance to the Traditional Chinese Medicine, the tongue is able to absolve a key role of a biosensor, while the different tongue regions are able to provide information to check the diagnosis the organ systems health [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The surface coating represents the exterior manifestation, which corresponds to the sustaining disease, and is the primary indication for the diagnosis making". In this way, the appropriate knowledge of the molecular aspects of tongue response is a key factor to comprehend this semeiotic medical practice [1,3,4]. Several studies on the microbiology of the healthy human tongue, through the sequencing of 16S rRNA, which is applied for the detection, categorization, and evaluation of the microbic charge within the biological mixtures, have shown that the most abundant phyla are Fusobacteria, Actinobacteria, Firmicutes, Proteobacteria, and Bacteroidetes [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations